Within and Outside the Black-Maghrebi Binary - Parikh, Shreya (Meridians, 2024)
Abstract What does it mean to be both Black and Tunisian, Black and Maghrebi, when the two identities are defined as different from each other, and in opposition with each other, in both North Africa and its diaspora? This article is an annotated conversation with Dr. Maha Abdelhamid, a Tunisian Black activist and scholar who has been crucial to the creation of the Black movement in Tunisia and Tunisian diaspora. This conversation examines the construction and negotiation of Tunisian-Black and Maghrebi-Black identities through Abdelhamid’s experiences of living in and working against racism in both Tunisia and France. It details Abdelhamid’s trajectory in becoming conscious of her Black and African identities, her complex relationship with her Arab identity, her role in building the Black movement in Tunisia after the 2011 revolution, and her arrival in France and experiences of exclusion in both Maghrebi diasporic as well as Black feminist civil society organizations. The interview points to the possible essentialization of Maghrebi and Black as separate identities not only in socio-political discourses that racialize and marginalize these groups, but also among groups challenging Islamophobia or anti-Blackness, leaving those with overlapping identities and racializing experiences outside their scope.
Keywords: Discrimination raciale

Le Moutchou (le battah) - Klein, Marc (Alger Etudiants, 1925)
Keywords: Discrimination raciale